Exploring the Individual Freedom of a Nonconformist Figure in Jerry Spinelli's Stargirl: A Sartrean Reading - Ervi Irawati (Lakon : Jurnal Kajian Sastra dan Budaya, 2026)
This study examines a nonconformist figure in Jerry Spinelli’s Stargirl through the Sartrean existentialist framework. It analyzes how Stargirl Caraway negotiates her freedom within a conformist social environment, focusing on her authenticity, the influence of social judgment, and her inner conflict between individuality and conformity. This study employs a qualitative method. Data are drawn from the novel's narrative and dialogues, supported by relevant scholarly sources. The analysis applies Sartrean existentialism, including existence precedes essence, freedom and responsibility, the look, being-for-others, bad faith, and being-for-itself. The findings show that Stargirl defines her existence through her choices and actions. However, social rejection leads her to temporarily conform and abandon her authenticity. She eventually returns to her authentic self, demonstrating that human existence is continuously shaped through conscious choices.